Mytilopsis leucophaeata, an alien dreissenid bivalve discovered in the Gulf of Gdańsk (southern Baltic Sea) - Anna Dziubińska (Oceanologia, 2011)
Mytilopsis leucophaeata (Conrad's false mussel), an invasive American bivalve, has been found for the first time in the Gulf of Gdańsk on hard substrata (PVC panels) deployed at depths from 3.5 to 6.0 m.